Copper-base metallurgy in Late Iron Age Cambodia: Evidence from Lovea. (June 2017) - Pryce, T.O.; O'Reilly, Dougald; Shewan, Louise
Abstract: In this paper we present the study of the copper-base assemblage of the Late Iron Age (c. 100–400 BC/AD) moated site of Lovea in north-western Cambodia. Fourteen artefacts, approximately 20% of the metals assemblage, including bracelets, rings and earrings, were analysed for their elemental and lead isotopic composition, and these data compared with existing Southeast Asian archaeometallurgical databases. Results indicate the presence of bronze, leaded bronze, and possibly high-tin bronze alloys on-site. The unleaded-bronzes exhibit a strong consistency with the lead isotope signature of Sepon in central Laos, a major prehistoric copper production centre. We propose that the apparent presence of a sole copper source, when others were available, may be linked to economic and/or cultural factors during a period of increasing social complexity. Highlights: Fourteen copper-base artefacts were studied from Late Iron Age (c. AD 100-400) Lovea in north-western Cambodia. Elemental and isotopic data for these bracelets, rings and earrings were compared with existing regional databases. Results indicate the presence of bronze, leaded bronze, and possibly high-tin bronze alloys on-site. Unleaded bronzes are consistent with the lead isotope signature of a prehistoric production centre in central Laos. The link to a single copper source, when others were available, requires further investigation.